Avaliação do comportamento físico, mecânico, térmico e energético de adobes com e sem estabilização - Gandia, Rômulo Marçal (2017)
The current construction sector presents high energy demand, natural resources and generates high volume of waste. As an example we have the products of the Industry of Glass Fiber Reinforced Polymers with (GFRP ) that produce great amount of discard. Another example is the generation of sludge by the Water Treatment Plants (WTPs). The adobe is a millenar ia n and current construction material . The revitalization is due to the characteri stics of sustainability, not sintering, low energy consumption and no use of cement in its composition. The challenges include water absorption, capillarity and compressive strength. "Synthetic Termite Saliva" (STS) is an excellent stabilizer of high cohesive and hydrophobic power. Therefore, the objective of this work is evaluate the incorporatio n of the GFRP residue, WTP waste and BCS into adobe, in terms of physical and mechanica l properties and to compare the energy consumption without stabilization with other conventional building materials. Each stabiliza tio n varies in four different proportions, according to the dry mass of the soil, plus a treatment without addition to the control . The adobe were subjected to tests of linear shrinkage, bulk density, water absorption, capillar ity, thermal conductivity and compressive strength tests by NTE.E0.80 and by the Brazilian Standard, in process. The best resul ts regarding the use of the GFRP residue were 7.5 and 10%, presenting more structured adobes, lower bul k density and better thermal comfort. The best results for the WTP -sludge residue were 1 and 3%. "Synthetic Termite Saliva" - STS, reduced capillarity and water absorption in relation to the control treatment. As for the energy consumption, the adobe without stabilizers presented better results in comparison to the concrete block, cast ceramic block and ceramic brick. The energy content of the adobe was 229.22 kJ kgˉ¹, corresponding to 8, 27 and 8% of the cast ceramic block, concrete block and ceramic bri ck, respectively. It was concluded that the use of stabilizers such as GFRP residue, WTP residue and STS should be used in the adobe`s production, because they improve its physical - mechanical and thermal properties and the energy consumption of the adobe presented better results in comparison to the conventional materials.